Complete genome sequence analysis of the multidrug resistant Aeromonas veronii isolated for the first time from stinging catfish (Shing fish) in Bangladesh - Rahman, Mohummad Muklesur; Sadekuzzaman, Mohammad; Rahman, Md Asikur; Siddique, Mahbubul Pratik; Uddin, Mohammad Asir; Haque, Md Enamul; Chowdhury, Md Golam Azam; Khasruzzaman, A K M; Rahman, Md Tanvir; Hossain, Muhammad Tofazzal; et al. (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Whole genome sequencing (WGS) of Aeromonas veronii Alim_AV_1000 isolated from ulcerative lesions of Shing fish (stringing catfish; Heteropneustes fossilis) was performed during the outbreak year 2021. Materials and Methods: Using next-generation sequencing (Illumina) technology, WGS was accomplished, resulting in the sequencing, assembly, and analysis of the entire genome of the A. veronii strain. Moreover, the genomic features, virulence factors, antimicrobial resistome, and phylogenetic analysis for the molecular evolution of this strain were also examined. Results: The genome size of the A. veronii Alim_AV_1000 strain was 4,494,515 bp, with an average G+C content of 58.87%. Annotation revealed the known transporters and genes linked to virulence, drug targets, and antimicrobial resistance. Conclusion: The findings of the phylogenetic analysis revealed that the strain of the present study has a close relationship with the China strain TH0426 and strain B56. This study provides novel information on A. veronii isolated from Shing fish in Bangladesh. J. Adv. Vet. Anim. Res., 10(3): 570–578, September 2023 http://doi.org/10.5455/javar.2023.j711